Computing protein near–UV circular dichroism spectra - Jasim, Sarah Badri (2020)
A fully quantitative theory connecting protein conformation and optical spectroscopy would facilitate deeper insights into biophysical and simulate studies of protein dynamics and folding. The regular, repeating, chiral nature of secondary structure elements leads to intense bands in the far-ultraviolet (UV). The near-UV bands are much weaker and have been challenging to compute theoretically. We report some advances in the accuracy of calculations in the near-UV by using the vibrational structure parameters in the circular dichroism (CD) spectra of proteins. The near-UV CD region is sensitive to electronic transitions in aromatic amino acids. This can be used to study local structural changes arising from processes such as a ligand binding to a protein. The improvements of the accuracy of the calculated spectra have been assessed over a set of eight proteins. The near-UV CD spectra have been calculated with the new parameters describing the aromatic side chain transitions. An improvement has been noticed for some calculated spectra. The contribution of individual chromophores to the CD spectra has been calculated. A detailed analysis has been presented for the tyrosine chromophores and the tryptophan chromophores, separately in different chapters. Further investigations have been conducted to study the interactions which are most important in determining the near-UV CD spectrum. An examination of the mechanisms has been made to understand the types of mechanisms which participate in generating the calculated spectra of the proteins in this thesis. The one-electron mechanism has the predominant role in generating the calculated spectra in the near-UV region. This mechanism appears mainly in all tyrosine and tryptophan chromophores. Some chromophores have shown coupling and mixing between their transitions through different mechanisms, i.e. the